Porous 3D carbon decorated Fe3O4 nanocomposite electrode for highly symmetrical supercapacitor performance - Lim, Y.S.; Lai, Chin Wei; Hamid, Sharifah Bee Abd (Royal Society of Chemistry, 2017)
In the present study, a hierarchical nanostructure of Fe3O4-porous hydrochar (p-Fe/HC) core shell nanocomposite was readily synthesized via a facile hydrothermal carbonization route followed by a KOH activation. In our new invention, hydrothermally formed core-shell nanoparticles underwent KOH activation to create micro- and mesopores forming porous hydrochar outer-shell on Fe3O4 nanoparticles core for improving capacitance performance. These porous structures eventually could act as potential electrolyte-accessible pathways which led to the contribution of pseudocapacitance connecting from the core (reaction at Fe3O4/electrolyte interface). Based on our electrochemical capacitive performance evaluation, p-Fe/HC nanocomposite electrode which comprised of 5 wt% Fe3O4 nanoparticles (±45 nm) could reach the specific capacitance of 259.3 F g-1 with a superior wide potential window of 1.8 V in 1 mol L-1 Na2SO4 aqueous electrolyte. By comparing KOH activation of pristine porous hydrochar and p-Fe/HC, an exceptionally high specific surface area (1712.8 m2 g-1) with bimodal type pores size distribution was observed. In addition, p-Fe/HC displayed a maximum energy density of 29.2 W h kg-1 at a power density of 1.2 kW kg-1, which is about 26% higher energy density than that of pristine porous hydrochar. In this manner, the synthesized porous hydrochar outer-shell could provide additional electrochemical stability to Fe3O4 core, preventing volume change at high current loading as well as conductive coating to enhance pseudocapacitance performance. Consequently, a symmetrical nanocomposite cell was successfully designed, with high capacitance retention of 95.1% after 5000 cycles.